ISOLATED TEAR OF POSTEROLATERAL BUNDLE OF ANTERIOR CRUCIATE LIGAMENT - Mazhar, Naveed; Saeed, Uzma (Journal of Ayub Medical College Abbottabad, 2018)
Anterior cruciate ligament injuries are very commonly encountered during routine MRI reporting and various signs have been described for their identification. However, the diagnosis of isolated bundle tears is difficult using MRI, thus can be easily overlooked, especially isolated tear of posterolateral bundle. We present a case of a young male with Gap and Footprint signs on MRI knee joint, which are considered highly specific of posterolateral ACL bundle tear. Keywords: Anterior cruciate ligament; Posterolateral bundle; Foot print sign; Gap sign; ACL partial tear